Antioxidant and cytotoxic activity of carotenes produced by Dunaliella salina under stress. (2nd October 2016) - Singh, Pritika; Baranwal, Manoj; Reddy, Sudhakara M.
Abstract: Context Dunaliella salina Teodoresco (Dunaliellaceae) is one of the promising microalgae consumed as food and medicine for many years. Objective Dunaliella salina was grown under different stress conditions for enhancing carotene production. The carotene enriched extract was evaluated for antioxidant and cytotoxic activity. Materials and methods Carotene content was calculated under salinity, nitrogen and temperature stress conditions. Antioxidant activity was determined through DPPH assay by incubating the samples for 45 min with 250 μg/mL of extract and reducing power assay was performed with 50, 100, 150 and 200 μg/mL of extract. Cytotoxicity was determined by incubating ∼2 × 10 4 MCF-7 (breast cancer) cells with 250 μg of extract in each well for 72 h by MTT assay. Result Carotene content was significantly increased to 9.8 (3.5 M NaCl), 13.9 (37 °C), 8.2 (250 mM KNO3 ) and 10.6 μg/mL (nitrogen-depleted medium) as compared with 3.2 μg/mL in normal conditions (1.7 M NaCl, 0.75 mM KNO3 and 28 °C). Free radical scavenging activity increased at 3.0 and 3.5 M NaCl (27.8 and 57.5%, respectively), 37 °C (31.4%) and in nitrogen-depleted medium (41.9%) compared with normal (15%) conditions. Carotene content and scavenging activity were positively correlated under salinity ( r  = 0.97), temperature ( r  = 0.85) and nitrogen ( r  = 0.7) stress conditions. Cytotoxicity against MCF-7 cell lines increased due to increase in carotene content suggesting that cytotoxicity may be associated with carotene accumulation. Discussion and conclusions Carotene content enhanced by D. salina under stress conditions increased the antioxidant and cytotoxic activity.